2020
DOI: 10.1177/1687814019900721
|View full text |Cite
|
Sign up to set email alerts
|

Study on magnetorheological nano-polishing using low-frequency alternating magnetic field

Abstract: With the development of electronics and optical industry, the high-efficiency ultra-precision polishing technologies of flat and curved surfaces are in high demand. The traditional magnetorheological polishing technology, using flexible polishing head, has the disadvantages of low polishing efficiency and small processing area. In this study, a novel tray-type magnetorheological polishing process using low-frequency alternating magnetic field excitation was developed to improve the efficiency of magnetorheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Wu et al [6] proposed a new method of disk-MRF with a low frequency alternating magnetic field. Lopez et al [16] have studied that the yield shear stress of magnetic particles under the action of the magnetic field is related to its deflection angle θ.…”
Section: Significancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [6] proposed a new method of disk-MRF with a low frequency alternating magnetic field. Lopez et al [16] have studied that the yield shear stress of magnetic particles under the action of the magnetic field is related to its deflection angle θ.…”
Section: Significancesmentioning
confidence: 99%
“…The relationship between yield shear stress m  and shear strain  of carbonyl iron powder chain is described by Equation (6). In order to obtain the relationship between the shear strain  and the workpiece rotation speed, Hegger et al [17] established the relationship between the rotation speed of the rotator and the shear strain as follows:…”
Section: Significancesmentioning
confidence: 99%
“…However, as magnetic grinding finishing involves point-contact polishing, the polishing area of the workpiece is very small, leading to low finishing efficiency. Yin and Wu proposed a disc-type magnetorheological finishing method using low-frequency alternating magnetic field excitation to enhance finishing efficiency [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…CMP can realize the smooth and flat processing of GaN crystals, but its efficiency needs to be improved further. Magnetorheological finishing is a non-damage processing technology [21][22][23][24][25], which can effectively realize sub-nanometer processing of hard and brittle crystal materials such as sapphire [26,27], silicon carbide [28,29], and optical glass [30][31][32]. However, research on GaN magnetorheological finishing has not been reported.…”
Section: Introductionmentioning
confidence: 99%